Services and global value chains: Some evidence on servicification of manufacturing and services networks - Rainer Lanz; Andreas Maurer (World Trade Organization (WTO), 2015)
This paper analyses the role of services in international trade through the lens of global value chains (GVCs). Services account for more than 70% of world GDP but only for around 20% of world trade in balance of payments terms. In value added terms, accounting for services embodied in exported goods, services account for 40% of world trade. However, the international supply of services is not only represented through cross-border transactions. Services are also traded through the movement of labour and capital. The latter contributes to the GDP of the domestic country. The services value added of foreign affiliates in selected EU countries account, on average, for a quarter of domestic services value added. The role of services as input into manufacturing production often termed servicification of manufacturing, is substantial with services value added accounting for almost a third of manufacturing exports in developed countries and 26% in developing economies. While the share of foreign services content in manufacturing exports is close to 12% in both developed and developing countries, the latter add significantly less domestic services value to their manufacturing exports. Services industries increasingly produce in networked or "fragmented" arrangements. The paper lays out conceptual and measurement issues related to services networks and provides evidence based on trade in value added statistics and on a case study on the film industry. In contrast to goods value chains, services networks appear less fragmented internationally based on trade in value added statistics and survey evidence. However, to better capture the international services fragmentation, advances in statistics by enterprise characteristics and by mode of supply, i.e. taking into account the movement of labour and capital, are required.
Keywords: D57; F14; F23; L23; L80; L82; 330; trade in value added; global value chains; services networks; trade in services